Psychopathic behavior in children’s characters: a study of psychoanalysis in short story of Membuat Senang Seekor Gajah - Novia Adibatus Shofah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The child character after doing the murder is seen to have no guilt but looks satisfied, happy, and proud. This study aims to analyze the psychopathic behaviour of the child characters in a short story, Membuat Senang Seekor Gajah, by Eka Kurniawan. In the analysis, the researcher uses Sigmund Freud's psychoanalytic theory and the concept of psychopathy to discuss psychopathic problems in child characters. Researchers use a pragmatic approach to find the meaning of psychopath in a short story. The results of this study indicate that the child character experiences an imbalance of id and ego, so they experience personality disorders, namely psychopaths. Child characters with psychopathic personalities cannot feel remorse, sadness, and fear of the sadism committed against the Elephant and are manipulative. Furthermore, the child characters enjoy mutilating animals to achieve personal satisfaction. Then, based on a pragmatic approach, depicting psychopaths in children is a contemporary criticism that describes a child's personality disorder due to unequal physical and mental health control.